How Nostalgic are You? : An Experientially-meaningful Communication of #NutrisariBernostalgia Campaign - Ardamas, Bayu Rustam; Yuliana, Mega; Pradipta, Ganuardi; Syarifa, Nabila; Astuti, Puji; Wiraditi, Ratu Balqis (Jobmark: Journal of Branding and Marketing Communication, 2021)
In communicating its iconic glass bottle edition of Nutrisari Jeruk, Nutrisari released an attractive advertisement on October 7, 2023. This advertisement also marks Nutrisari's 45th anniversary. This advertising approach exploits longing and curiosity and evokes specific memories about when not everyone could enjoy this 'expensive' and 'exclusive' drink product. Tne could enjoy these 'expensive' and 'exclusive' beverage products. The copywriting also includes the importance of nostalgia, citing expert statements. By highlighting audience comments via Nutrisari's social media accounts, this article discusses the relatability of Nutrisari's nostalgic messages from the perspective of Komunikasi Berasa (experientially-meaningful communication) theory with its six dimensions (Wijaya, 2009): sensorial meaningfulness, emotional, rational, relevant, beneficial, and social. This study can be a reflection for brands in optimizing the meaningfulness of their campaign messages to be more connected and relevant to their consumer audiences.